Secure energy outage analysis of UAV swarm-based network. - Tien Hoa Nguyen; Hoang Vu Tran (PLoS ONE)
In the pursuit of enhancing energy-efficient and secure communications, this study explores secure energy outage probability (SEP) within unmanned aerial vehicle (UAV) swarm-based energy harvesting networks. UAVs, often deployed as relay nodes to facilitate communication between a source and a destination, face significant security and energy efficiency challenges, particularly when relying on battery-free configurations. These UAVs must simultaneously harvest energy from ambient sources and thwart eavesdropping attempts from external interceptors, demanding secure solutions for efficient operation. To address these challenges, we propose two energy-efficient secure UAV selection methods aimed at optimizing the communication network's physical layer security. The first method prioritizes maximizing the communication link quality between the source and the selected UAV, while the second method focuses on minimizing the link quality between the UAV and the eavesdropper. Through these strategies, the study targets improved SEP performance without compromising energy efficiency, ensuring sustainable network operation. The study evaluates the effectiveness of these methods through rigorous mathematical frameworks in both approximate and asymptotic forms. Through numerical analyses, our proposed methods demonstrate notable improvements in SEP performance. Specifically, we observe that SEP increases significantly when the transmit signal-to-noise ratio (SNR) is varied from low to medium values; however, the benefits taper off at higher SNR ranges, indicating a performance plateau. Moreover, introducing a larger number of UAVs in the swarm enhances SEP, showcasing the scalability advantage of the proposed methods. Further insights reveal that configuring a higher power-splitting coefficient enhances SEP at lower SNR values, although it yields diminishing returns at higher SNR levels. Additionally, our findings highlight the influence of UAV placement, with closer proximity to the destination improving SEP performance. However, there exists an optimal flying altitude for UAVs that minimizes SEP, offering a balance between security enhancement and energy efficiency. These results underscore the superiority of the proposed methods in addressing the dual challenges of physical layer security and energy conservation.